Identification of a recurrent mutation in the protoporphyrinogen oxidase gene in swiss patients with variegate porphyria: Clinical and genetic implications - Van TuylL Van Serooskerke, A M; Schneider-Yin, X; Schimmel, R J; Bladergroen, R S; Barman, J; Poblete-Gutiérrez, P; Van Geel, M; Frank, J; Minder, E I (Cellular and Molecular Biology, 2009)
Variegate porphyria (VP), one of the acute hepatic porphyrias, results from an autosomal dominantly inherited deficiency of protoporphyrinogen oxidase (PPOX), the seventh enzyme in heme biosynthesis. Affected individuals can develop both cutaneous symptoms and potentially life-threatening neurovisceral attacks. Thirty unrelated VP index patients and families are currently known in the Swiss Porphyrin Reference Laboratory in Zürich. In 16 of a total of 24 genetically tested families, we detected a recurrent mutation in the PPOX gene, designated 1082-1083insC, reflecting a prevalence of 67%. Haplotype analysis revealed that 1082-1083insC arose on a common genetic background and, thus, represents a novel founder mutation in the Swiss population. Knowledge on the carrier status within a family does not only allow for adequate genetic counseling but also for prevention of the potentially life-threatening acute porphyric attacks. Hence, future molecular screening in Swiss VP patients might be facilitated by first seeking for mutation 1082-1083insC.